Objective quantification of BCL2 protein by multiplex immunofluorescence in routine biopsy samples of diffuse large B-cell lymphoma demonstrates associations with survival and BCL2 gene alterations. Issue 6 (11th May 2020) - Chen, Lina; Tyryshkin, Kathrin; Moore, Alison; Scott, David W.; Steidl, Christian; Li, Yi; Shepherd, Lois E.; Rauh, Michael; Deng, Lan; Good, David; Virk, Shakeel; Chen, Bingshu E.; et al.
Abstract: Up-regulation of BCL2 in cases of diffuse large B-cell lymphoma (DLBCL) can confer treatment resistance. Quantitative immunofluorescence (QIF) histology allows objective quantification of protein-based biomarkers. We investigated the utility of QIF for evaluating BCL2 as a biomarker in DLBCL by quantifying BCL2 selectively in CD20-expressing lymphoma cells in biopsy samples from 116 cases of DLBCL in two cohorts one of which consisted of relapsed/refractory cases from a clinical trial. BCL2 protein by QIF correlated with BCL2 mRNA abundance and was associated with both translocation and copy number gain of the BCL2 gene. Elevated BCL2 protein expression by QIF, but not immunohistochemistry or mRNA quantification, was associated with inferior overall and relapse-free survival in the relapsed/refractory cohort. QIF is an effective means of quantifying BCL2 protein objectively in routine cancer biopsy specimens and shows promise for identifying relapsed/refractory DLBCL patients at risk of inferior outcomes after salvage therapy.